CT Imaging of Craniofacial Fibrous Dysplasia - Zerrin Unal Erzurumlu; Peruze Celenk; Emel Bulut; Yakup Sancar Barıs (Case Reports in Dentistry)
Fibrous dysplasia is a benign fibroosseous bone dysplasia that can involve single (monostotic) or multiple (polyostotic) bones. Monostotic form is more frequent in the jaws. It is termed as craniofacial fibrous dysplasia, when it involves, though rarely, adjacent craniofacial bones. A 16-year-old girl consulted for a painless swelling in the right posterior mandible for two years. Panoramic radiography revealed ground-glass ill-defined lesions in the three different regions of the maxilla and mandible. Axial CT scan (bone window) showed multiple lesions involving skull base and facial bones. Despite lesions in the skull base, the patient had no abnormal neurological findings. The lesion was diagnosed as fibrous dysplasia based on radiological and histopathological examination. In this paper, CT findings and differential diagnosis of CFD are discussed. CT is a useful imaging technique for CFD cases.